2022
DOI: 10.1007/s11914-022-00734-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of COVID-19 on Musculoskeletal Health

Abstract: Purpose of Review Although COVID-19 was originally characterized as a respiratory disease, recent findings have shown lingering side effects in those who have recovered, and much is still unknown about the long-term consequences of the illness. Thus, the potential of unearthing multi-system dysfunction is high, with current data revealing significant impacts on musculoskeletal health. Recent Findings Multiple animal models of COVID-19 infection have revealed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 131 publications
1
9
0
Order By: Relevance
“…Qiao et al demonstrated that bone loss is associated with SARS-CoV-2-induced cytokine dysregulation, as circulating proinflammatory cytokines not only upregulate osteoclastic differentiation in bone tissues but also trigger an amplified proinflammatory cascade in skeletal tissues to augment their pro-osteoclastogenesis effect ( 29 ). It has been suggested that hypoxia and oxidative stress may play a role in the development of osteoporosis in COVID-19 patients ( 30 ). Severe COVID-19-induced hypoxemia can trigger the excessive production of reactive oxygen species (ROS), which disrupts the balance of redox homeostasis ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qiao et al demonstrated that bone loss is associated with SARS-CoV-2-induced cytokine dysregulation, as circulating proinflammatory cytokines not only upregulate osteoclastic differentiation in bone tissues but also trigger an amplified proinflammatory cascade in skeletal tissues to augment their pro-osteoclastogenesis effect ( 29 ). It has been suggested that hypoxia and oxidative stress may play a role in the development of osteoporosis in COVID-19 patients ( 30 ). Severe COVID-19-induced hypoxemia can trigger the excessive production of reactive oxygen species (ROS), which disrupts the balance of redox homeostasis ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This condition may develop from coagulopathy, a critical illness of the virus, medications such as cortisone, direct infection of bone marrow macrophages, an autoimmune reaction with inflammation, oxidative stress, or hypoxia. [22][23][24]…”
Section: Bone Lossmentioning
confidence: 99%
“…In patients after recovery from severe acute respiratory syndrome (SARS), osteonecrosis and other bone changes with reduced bone density were observed, 130 which were partly but not fully explained by corticosteroid treatment, the severity of infection, or several comorbidities that markedly increase the production of inflammatory mediators. 131 Significantly higher serum concentrations of pro- and anti-inflammatory cytokines, including IL-6, tumor necrosis factor-α, and IL-10, suggest that disease severity may be associated with a ‘cytokine storm’. Several cytokines, in particular RANKL, play a fundamental role in osteoclastogenesis in physiological and pathological conditions.…”
Section: Bone Fragility and Age-related Bone Alterations In The Covid...mentioning
confidence: 99%